Dialog Lintas Agama: Hambatan Komunikasi Antariman - Dermawan, Herman; Herman (IKHBAR: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
Interfaith dialogue plays a crucial role in promoting understanding, tolerance, and peaceful coexistence in pluralistic societies. However, these dialogue efforts are often hampered by various barriers to interfaith communication. This article aims to identify and analyze these barriers, including theological differences, cognitive biases and stereotypes, identity politics, and a lack of religious education and literacy. Using a qualitative approach and extensive literature review, this research highlights how these factors inherently influence the dynamics of dialogue and hinder the achievement of shared goals. The author argues that a deeper understanding of these barriers is an essential first step in formulating more effective dialogue strategies, based on the principles of mutual respect, empathy, and a willingness to listen. These findings are expected to contribute to dialogue practitioners, academics, and policymakers in facilitating more constructive and sustainable interfaith communication.